Biomechanical Determination of Distal Level for Fusions across the Cervicothoracic Junction - Cheng, Ivan (Global Spine J, 2015)
Study Design In vitro testing. Objective To determine whether long cervical and cervicothoracic fusions increase the intradiscal pressure at the adjacent caudal disk and to determine which thoracic end vertebra causes the least increase in the adjacent-level intradiscal pressure. Methods A bending moment was applied to six cadaveric cervicothoracic spine specimens with intact rib cages. Intradiscal pressures were recorded from C7–T1 to T9–10 before and after simulated fusion by anterior cervical plating and posterior thoracic pedicle screw constructs. The changes in the intradiscal pressure from baseline were calculated and compared. Results No significant differences where found when the changes of the juxtafusion intradiscal pressure at each level were compared for the flexion, extension, and left and right bending simulations. However, combining the pressures for all directions of bending at each level demonstrated a decrease in the pressures at the T2–T3 level. Exploratory analysis comparing changes in the pressure at T2–T3 to other levels showed a significant decrease in the pressures at this level (p = 0.005). Conclusions Based on the combined intradiscal pressures alone it may be advantageous to end long constructs spanning the cervicothoracic junction at the T2 level if there are no other mitigating factors.